KECEMASAN BERBICARA DI DEPAN UMUM DITINJAU DARI KEPERCAYAAN DIRI DAN KEAKTIFAN DALAM ORGANISASI KEMAHASISWAAN - Bukhori, Baidi (Jurnal Komunikasi Islam, 2016)
The purposes of this study are: 1) To examine the influence of self confidence to the nervousness in public speaking, and 2) To examine the difference of nervousness in public speaking between the activists of student organization and those who were not. The population of this study was the students of Da’wah and Communication Faculty of Walisongo State Islamic University Semarang. Sampling was done by using stratified sampling technique. The instrument of data collection used in this study was the scale of nervousness in public speaking and the scale of self confidence. The data were analyzed by using simple regression analysis and test t. the conclusion of this study were: 1) There was the influence of self confidence to the nervousness in public speaking. 2) There was the difference of nervousness in public speaking between the activists of student organization and those who were not.